THEORETICAL MARKET FRAMEWORK FOR MARKET-BASED TSO–DSO IN REAL-WORLD IMPLEMENTATIONS (International Journal of Food and Nutritional Sciences, 2022)
This paper introduces aTheoretical Market Framework (TMF) forconceptualizing and designing electricity markets,integrating Transmission System Operator AndDistribution System Operator (TSO–DSO)coordination mechanisms.